Blasius–Rayleigh–Stokes flow of nanofluid past an isothermal magnetized surface - Ishaq, Airal; Ahmad, Adeel (Advances in mechanical engineering, 2021)
The present article investigated the unsteady flow of a nanofluid past an isothermal magnetized plate emanating from a moving slot. This unique form of unsteady boundary layer flow is analogous to stretching/shrinking sheet problems subject to the direction of motion of the slot. Governing partial differential equation can be reduced into a similar form using the Blasius–Rayleigh–Stokes variable. The consequences of the movable slot and magnetic field on flow and heat transfer of nanofluid are examined by solving the problem numerically. The behavior of the magnetic field in the presence of nanoparticles is also examined. Effects of the magnetic field upon the existence of dual solutions for the specific range of moving slot parameter are also studied in detail.